Solid electrolyte, electricity storage element, and method for producing solid electrolyte
By adjusting the molar ratio of lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine, a solid electrolyte with a specific crystal structure is prepared, which solves the problem of reduced productivity when sulfide solid electrolytes improve crystallinity, and achieves high ion conduction The charge and discharge performance of solid electrolytes and power storage components is improved.
Patent Information
- Application Number
- CN202380034449.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-19
- Filing Date
- 2023-04-18
- Publication Date
- 2024-12-17
AI Technical Summary
The problem of the reduction in productivity when the conventional sulfide solid electrolyte is improved.
By adjusting the molar ratio of lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine, a solid electrolyte with a specific crystal structure is prepared, which reduces the precipitation temperature of the high ionic conductivity crystal phase and improves productivity.
The generation of high ion conductivity crystal phases precipitated at lower temperatures is achieved, the productivity and ion conductivity of solid electrolytes are improved, and the charge and discharge performance of the power storage element is enhanced.
Smart Images

Figure CN119156676A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte, a power storage element, and a method for producing the solid electrolyte. Background Art
[0002] The non-aqueous electrolyte secondary battery represented by the lithium ion secondary battery is widely used in electronic equipment such as personal computers, communication terminals, and automobiles due to its high energy density. The above-mentioned non-aqueous electrolyte secondary battery is generally composed of an electrode body including a pair of electrodes and a separator, a non-aqueous electrolyte, and a container for accommodating these electrode bodies and the non-aqueous electrolyte, and is charged and discharged by the transfer of charge transport ions between the two electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and double electric layer capacitors have also been widely popularized.
[0003] In recent years, a storage element using a solid electrolyte such as a sulfide solid electrolyte as a non-aqueous electrolyte has been proposed instead of a non-aqueous electrolyte solution obtained by dissolving an electrolyte salt in a liquid such as an organic solvent. Patent Document 1 describes a sulfide solid electrolyte containing Li, P, S, N, and an element X (X is at least one element selected from Cl, Br, and I) as constituent elements and having a crystal structure.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2020 / 045634 Summary of the invention
[0007] It is known that a sulfide solid electrolyte containing Li, P, S, N and the above-mentioned element X as constituent elements generates a crystal phase with high ion conductivity having diffraction peaks at 2θ=19.9° and 29.3° in an X-ray diffraction pattern using CuKα rays. However, if the heat treatment temperature is increased in order to improve the crystallinity of this crystal phase, there is a risk of reduced productivity.
[0008] The present invention has been made based on the above circumstances, and an object of the present invention is to provide a solid electrolyte and a power storage element capable of improving productivity.
[0009] A solid electrolyte according to one aspect of the present invention is a solid electrolyte having a crystal structure containing lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine as constituent elements, wherein the molar ratio of the lithium to the phosphorus is r 1 , the molar ratio of the sum of the bromine and the iodine to the phosphorus is r 2 , the molar ratio of the sum of the bromine and the iodine to the nitrogen is r 3 , the following conditions (a), (b) or (c) are met.
[0010] (a) 3.00≤r 1 -r 2 ≤3.60 and 1.5≤r 3 ≤100
[0011] (b)2.80≤r 1 -r 2 <3.00 and 2.0≤r 3 ≤100
[0012] (c)2.60≤r 1 -r 2 <2.80 and 2.5≤r 3 ≤100
[0013] A power storage device according to another aspect of the present invention includes the solid electrolyte.
[0014] A method for producing a solid electrolyte according to another aspect of the present invention comprises the following steps: preparing a composition containing lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine as constituent elements; and treating the composition; setting the molar ratio of the lithium to the phosphorus to r 1 , the molar ratio of the sum of the bromine and the iodine to the phosphorus is r 2 , the molar ratio of the sum of the bromine and the iodine to the nitrogen is r 3 , the following conditions (a), (b) or (c) are met.
[0015] (a) 3.00≤r 1 -r 2 ≤3.60 and 1.5≤r 3 ≤100
[0016] (b)2.80≤r 1 -r 2 <3.00 and 2.0≤r 3 ≤100
[0017] (c)2.60≤r 1 -r 2 <2.80 and 2.5≤r 3 ≤100
[0018] According to any aspect of the present invention, a solid electrolyte and a power storage element capable of improving productivity can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic cross-sectional view of an all-solid-state battery as one embodiment of the electric storage element of the present invention.
[0020] Figure 2This is a schematic diagram showing a power storage device configured by combining a plurality of power storage elements according to an embodiment of the present invention. DETAILED DESCRIPTION
[0021] First, the outline of the solid electrolyte disclosed in this specification is described.
[0022] [1] A solid electrolyte according to one aspect of the present invention is a solid electrolyte having a crystal structure containing lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine as constituent elements, wherein the molar ratio of the lithium to the phosphorus is r 1 , the molar ratio of the sum of the bromine and the iodine to the phosphorus is r 2 , the molar ratio of the sum of the bromine and the iodine to the nitrogen is r 3 , the following conditions (a), (b) or (c) are met.
[0023] (a) 3.00≤r 1 -r 2 ≤3.60 and 1.5≤r 3 ≤100
[0024] (b)2.80≤r 1 -r 2 <3.00 and 2.0≤r 3 ≤100
[0025] (c)2.60≤r 1 -r 2 <2.80 and 2.5≤r 3 ≤100
[0026] The solid electrolyte described in [1] above can improve productivity. More specifically, in the solid electrolyte described in [1] above, the precipitation temperature of the high ion conductivity crystalline phase precipitated by heat treatment is low. When heat treatment is performed during the manufacture of the solid electrolyte described in [1] above, a high ion conductivity crystalline phase (hereinafter also referred to as HICP: High Ion Conduction Phase) having diffraction peaks at 2θ=19.9° and 29.3° in the X-ray diffraction pattern using CuKα rays can be precipitated. It is believed that when the heat treatment temperature is increased, the HICP is transformed into a crystalline phase having diffraction peaks at diffraction angles of 2θ=21.0° and 28.0° in the X-ray diffraction pattern using CuKα rays (hereinafter also referred to as LICP: Low Ion Conduction Phase), and when the heat treatment temperature is further increased, the HICP is transformed into β-Li 3 PS 4 In HICP, LICP and β-Li 3 PS 4Among them, HICP and LICP have higher ionic conductivity, and β-Li 3 PS 4 The ion conductivity of HICP, LICP and β-Li 3 PS 4 Among them, HICP has the highest ion conductivity. Therefore, it is necessary to control the heat treatment temperature to promote the formation of HICP or LICP (hereinafter also referred to as HICP, etc.) and not to easily generate β-Li 3 PS 4 Therefore, the precipitation temperature of the crystal phase with high ion conductivity such as HICP is low, and the heat treatment temperature can be lowered, thereby improving productivity.
[0027] The reason why the precipitation temperature of HICP, etc. is low in the solid electrolyte described in [1] above is still uncertain, but it is speculated to be the following reasons. According to the views of the inventors, in previous solid electrolytes, when the nitrogen content increases, the precipitation temperature of HICP, etc. increases. On the other hand, bromine and iodine contribute to the formation of HICP, etc., so it is believed that by containing both bromine and iodine, HICP, etc. is more easily formed. Therefore, the solid electrolyte described in [1] above contains more bromine and iodine, and the molar ratio of the sum of bromine and iodine to nitrogen is within an appropriate range, so the precipitation temperature of HICP, etc. can be effectively reduced. In addition, it is believed that even if a certain amount of lithium that is not considered to be combined with bromine and iodine is contained, the formation of HICP, etc. is promoted. Therefore, it is speculated that by controlling the molar ratio of the constituent elements of the solid electrolyte within the above range, bromine and iodine and the above lithium act in a manner that synergistically reduces the precipitation temperature of HICP, etc.
[0028] [2] In the solid electrolyte described in [1] above, the molar ratio of the nitrogen to the phosphorus may be 0.01 to 0.45. Thus, the solid electrolyte described in [2] above forms a path that is conducive to lithium ion conduction in the crystal structure by controlling the molar ratio of the nitrogen to the phosphorus within the above range, thereby improving ion conductivity.
[0029] [3] The solid electrolyte described in [1] or [2] above can be represented by the following formula 1.
[0030] Li a PAl b S c N d Br e I f ···1
[0031] In the above formula 1, a, b, c, d, e and f are numerical values giving a stoichiometric ratio, a is a numerical value satisfying 3.00<a<5.30, b is a numerical value satisfying 0.00<b<0.40, c is a numerical value satisfying 3.50<c<4.20, d is a numerical value satisfying 0.00<d<0.60, e is a numerical value satisfying 0.00<e<2.20, and f is a numerical value satisfying 0.00<f<2.20. Thus, by expressing the solid electrolyte described in [3] by the above formula 1, the precipitation temperature of HICP etc. can be easily lowered.
[0032] [4] The solid electrolyte described in any one of [1] to [3] above may have a plurality of crystallization temperatures in the range of 150°C to 400°C, and when the lowest of the plurality of crystallization temperatures is set to T1[°C], and the highest of the plurality of crystallization temperatures is set to T2[°C], the difference {T2-T1} between the crystallization temperature T1 and the crystallization temperature T2 is 50°C or more. Here, the crystallization temperature T1 refers to the precipitation temperature of HICP and the like. Depending on the composition, the solid electrolyte described in [4] above may precipitate LICP instead of HICP during heat treatment. Therefore, the crystallization temperature T1 refers to the precipitation temperature of HICP when HICP is precipitated, and refers to the precipitation temperature of LICP when HICP is not precipitated. In addition, the crystallization temperature T2 refers to the precipitation temperature of β-Li 3 PS 4 or β-Li 3 PS 4 Therefore, by setting the difference {T2-T1} between the crystallization temperature T1 and the crystallization temperature T2 to 50°C or more, the thermal stability of HICP and the like can be improved.
[0033] [5] The solid electrolyte described in any one of [1] to [4] may include at least one of a crystal structure A having diffraction peaks at 2θ=19.9°±0.5° and 29.3°±0.5° in an X-ray diffraction pattern using CuKα rays, and a crystal structure B having diffraction peaks at diffraction angles of 2θ=21.0±0.5° and 28.0±0.5° in the X-ray diffraction pattern. The crystal structure A refers to the crystal structure of HICP, and the crystal structure B refers to the crystal structure of LICP. Therefore, the solid electrolyte described in [5] can further improve ion conductivity by including at least one of the crystal structure A and the crystal structure B.
[0034] [6] The solid electrolyte described in [5] may include the crystal structure A. The solid electrolyte described in [6] may further improve ion conductivity by including the crystal structure A.
[0035] [7] The ion conductivity of the solid electrolyte described in any one of [1] to [6] at 25°C may be 2.0×10 -3 S / cm or more. The ion conductivity at 25°C of the solid electrolyte described in [7] is 2.0×10 -3 S / cm or more, the charge and discharge performance of the energy storage device including the solid electrolyte described in [7] above can be improved.
[0036] [8] An electric storage device according to another aspect of the present invention includes the solid electrolyte according to any one of [1] to [7] above.
[0037] Since the energy storage device described in [8] above includes the solid electrolyte described in any one of [1] to [7] above, productivity can be improved.
[0038] [9] A method for producing a solid electrolyte according to another aspect of the present invention comprises the following steps: preparing a composition containing lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine as constituent elements; and treating the composition; setting the molar ratio of the lithium to the phosphorus to r 1 , the molar ratio of the sum of the bromine and the iodine to the phosphorus is r 2 , the molar ratio of the sum of the bromine and the iodine to the nitrogen is r 3 , the following conditions (a), (b) or (c) are met.
[0039] (a) 3.00≤r 1 -r 2 ≤3.60 and 1.5≤r 3 ≤100
[0040] (b)2.80≤r 1 -r 2 <3.00 and 2.0≤r 3 ≤100
[0041] (c)2.60≤r 1 -r 2 <2.80 and 2.5≤r 3 ≤100
[0042] The method for producing a solid electrolyte described in [9] above can improve productivity.
[0043] It should be noted that in the present invention, having a crystal structure can be confirmed by powder X-ray diffraction measurement. That is, "having a crystal structure" means that a peak from the crystal structure of the solid electrolyte is observed in the X-ray diffraction pattern obtained by powder X-ray diffraction measurement. The solid electrolyte may contain an amorphous portion. The powder X-ray diffraction measurement is carried out according to the following steps. In an airtight X-ray diffraction measurement sample holder, the solid electrolyte powder for measurement is filled in an argon atmosphere with a dew point below -50°C. Powder X-ray diffraction measurement is performed using an X-ray diffraction device ("MiniFlex II" from Rigaku). The ray source is CuKα rays, the tube voltage is 30kV, the tube current is 15mA, and the diffracted X-rays pass through a Kβ filter with a thickness of 30μm and are detected with a high-speed one-dimensional detector (model: D / teX Ultra 2). The sampling width is 0.01°, the scanning speed is 5° / min, the divergence slit width is 0.625°, the receiving slit width is 13 mm (OPEN), and the scattering slit width is 8 mm. In addition, in the present invention, "X-ray diffraction pattern using CuKα rays" refers to the X-ray diffraction pattern obtained by the above-mentioned powder X-ray diffraction measurement. Furthermore, in the present invention, the "crystallization temperature" of the solid electrolyte is obtained by measurement using a differential scanning calorimeter (DSC) according to the following steps. In an argon atmosphere with a dew point below -50°C, the sample powder for measurement (the solid electrolyte before heat treatment such as the composition prepared in the manufacturing method of the solid electrolyte) is put into a SUS sealed dish, and then sealed with a special clamp. Differential scanning calorimetry is performed using a DSC device ("Thermo Plus DSC8230" from Rigaku). The temperature range is from room temperature to 400°C, and the heating rate is 10°C / min.
[0044] In the present invention, the ion conductivity is obtained by measuring the AC impedance by the following method. In an argon atmosphere with a dew point below -50°C, 120 mg of sample powder is put into a powder molding machine with an inner diameter of 10 mm, and then uniaxial pressure molding is performed at a pressure below 50 MPa using a hydraulic press. After the pressure is released, 120 mg of SUS316L powder as a collector is put on the top of the sample, and uniaxial pressure molding is performed again at a pressure below 50 MPa using a hydraulic press. Next, 120 mg of SUS316L powder as a collector is put on the bottom of the sample, and uniaxial pressure molding is performed at 360 MPa for 5 minutes to obtain particles for measuring ion conductivity. The particles for measuring ion conductivity are inserted into a HS battery manufactured by Hohsen Corporation, and AC impedance measurement is performed at a specified temperature. The measurement conditions are an applied voltage amplitude of 20 mV, a frequency range of 1 MHz to 100 mHz, and a measurement temperature of 25°C.
[0045] A solid electrolyte, a method for manufacturing a solid electrolyte, a storage element, a method for manufacturing a storage element, a storage device, and other embodiments of an embodiment of the present invention are described in detail. It should be noted that the names of the components (constituent elements) used in each embodiment are sometimes different from the names of the components (constituent elements) used in the background art.
[0046] <Solid electrolyte>
[0047] (Crystal Structure)
[0048] The solid electrolyte of one embodiment of the present invention has a crystal structure. The solid electrolyte preferably includes at least one of a crystal structure (HICP) having diffraction peaks at 2θ=19.9°±0.5° and 29.3°±0.5° in an X-ray diffraction pattern using CuKα rays, and a crystal structure (LICP) having diffraction peaks at diffraction angles 2θ=21.0±0.5° and 28.0±0.5° in the above X-ray diffraction pattern. In addition, the solid electrolyte more preferably includes HICP. When the solid electrolyte includes HICP, etc., good ion conductivity can be exerted.
[0049] The solid electrolyte may have a crystal structure other than HICP and LICP. Examples of the crystal structure other than HICP and LICP include β-Li 3 PS 4 , LGPS type, argyrodite type, Li 7 P 3 S 11 , Thio-LISICON series, etc. The solid electrolyte may have an amorphous portion.
[0050] In one embodiment of the solid electrolyte, β-Li has diffraction peaks in the range of diffraction angles 2θ of 17.5°±0.5°, 18.1°±0.5°, 29.1°±0.5°, 29.9°±0.5°, and 31.2°±0.5° in an X-ray diffraction pattern using CuKα rays. 3 PS 4 The content of is less than that of HICP and the like. In this case, the ion conductivity of the solid electrolyte is further improved.
[0051] In one embodiment of the solid electrolyte, the content of LICP is preferably less than that of HICP. In this case, the ion conductivity of the solid electrolyte is further improved.
[0052] In the X-ray diffraction pattern of the solid electrolyte using CuKα rays, the diffraction peak intensity I from HICP in the range of the diffraction angle 2θ of 19.9°±0.5° HRelative to β-Li 3 PS 4 The diffraction peak intensity I in the range of diffraction angle 2θ of 17.5°±0.5° β The intensity ratio I H / I β The lower limit of is preferably 1, more preferably 2. Strength ratio I H / I β The HICP and β-Li contained in the solid electrolyte 3 PS 4 The intensity ratio I H / I β There is no particular upper limit on the β When it is 0, the above intensity ratio I H / I β Infinity is included in being greater than 1.
[0053] In the X-ray diffraction pattern of the solid electrolyte using CuKα rays, the diffraction peak intensity I from LICP in the range of diffraction angle 2θ of 21.0°±0.5° L Relative to the above diffraction peak intensity I β The intensity ratio I L / I β The lower limit of is preferably 1, more preferably 2. Strength ratio I L / I β The LICP and β-Li contained in the solid electrolyte 3 PS 4 The intensity ratio I L / I β There is no particular upper limit on the β When it is 0, the above intensity ratio I L / I β Infinity is included in being greater than 1.
[0054] In the X-ray diffraction pattern of the solid electrolyte using CuKα rays, the diffraction peak intensity I H Relative to the above diffraction peak intensity I L The intensity ratio I H / I L The lower limit of is preferably 1, more preferably 2. Strength ratio I H / I L It is related to the existence ratio of HICP and LICP contained in the solid electrolyte. H / I L There is no particular upper limit on the L When it is 0, the above intensity ratio I H / I L Infinity is included in being greater than 1.
[0055] The solid electrolyte has a plurality of crystallization temperatures in the range of 150°C to 400°C, and when the lowest crystallization temperature among the plurality of crystallization temperatures is set to T1[°C], and the highest crystallization temperature among the plurality of crystallization temperatures is set to T2[°C], the lower limit of the difference {T2-T1} between the crystallization temperature T1 and the crystallization temperature T2 is preferably 50°C, more preferably 60°C, further preferably 70°C, and further preferably 80°C. By making the difference {T2-T1} between the temperature T1 and the temperature T2 equal to or greater than the lower limit, the thermal stability of HICP and the like can be improved. It should be noted that the upper limit of the difference {T2-T1} between the temperature T1 and the temperature T2 is not particularly limited, and may be, for example, 150°C.
[0056] (composition)
[0057] A solid electrolyte according to one embodiment of the present invention contains lithium, phosphorus, sulfur, aluminum, nitrogen, bromine, and iodine as constituent elements.
[0058] In one embodiment of the solid electrolyte, regarding the constituent elements of the solid electrolyte, the molar ratio of lithium to phosphorus is set to r 1 , the molar ratio of the sum of bromine and iodine to phosphorus is r 2 When r 1 -r 2 The lower limit of r is 2.60, preferably 2.75, and more preferably 2.90. 1 -r 2 The upper limit of r is 3.60, more preferably 3.40, and further preferably 3.20. 1 -r 2 If the above lower limit is exceeded, the proportion of lithium not combined with bromine and iodine is insufficient, so HICP and the like are difficult to precipitate. 1 -r 2 If the above upper limit is exceeded, the ratio of the lithium exceeds the range suitable for forming HICP, and HICP and the like are difficult to precipitate.
[0059] Regarding the constituent elements of the solid electrolyte, when the above r 1 -r 2 When the molar ratio of the sum of bromine and iodine to nitrogen is 3.00 or more and less than 3.60, 3 The lower limit of the molar ratio is 1.5, preferably 1.6. 3 The upper limit of the molar ratio is 100, preferably 5.1, more preferably 3.0, and further preferably 2.0. 3 If the molar ratio is less than the above lower limit, the ratio of bromine and iodine that contribute to the formation of HICP etc. is small, so it is difficult to lower the precipitation temperature of HICP etc.3 If the above upper limit is exceeded, the thermal stability of HICP etc. decreases. The reason is not clear, but it is estimated that when the ratio of bromine and iodine exceeds a certain amount, they cannot stably exist in the crystal structure of HICP etc., thus promoting the collapse of the crystal structure.
[0060] Regarding the constituent elements of the solid electrolyte, when the above r 1 -r 2 When the molar ratio of the sum of bromine and iodine to nitrogen is 2.80 or more and less than 3.00, the molar ratio of the sum of bromine and iodine to nitrogen is 3 The lower limit of the molar ratio is 2.0, preferably 2.1. 3 The upper limit of the molar ratio is 100, preferably 5.1, more preferably 3.0, and further preferably 2.3. 3 If the molar ratio is less than the above lower limit, the ratio of bromine and iodine that contribute to the formation of HICP etc. is small, so it is difficult to lower the precipitation temperature of HICP etc. 3 If the above upper limit is exceeded, the thermal stability of HICP and the like decreases.
[0061] Regarding the constituent elements of the solid electrolyte, when the above r 1 -r 2 When the molar ratio of the sum of bromine and iodine to nitrogen is 2.60 or more and less than 2.80, the molar ratio of the sum of bromine and iodine to nitrogen is 3 The lower limit of the molar ratio is 2.5, preferably 2.6. 3 The upper limit of the molar ratio is 100, preferably 5.1, more preferably 3.0, and further preferably 2.8. 3 If the molar ratio is less than the above lower limit, the ratio of bromine and iodine that contribute to the formation of HICP etc. is small, so it is difficult to lower the precipitation temperature of HICP etc. 3 If the above upper limit is exceeded, the thermal stability of HICP and the like decreases.
[0062] Regarding the constituent elements of the solid electrolyte, the lower limit of the molar ratio of nitrogen to phosphorus is preferably 0.01, more preferably 0.03, and further preferably 0.05. On the other hand, the upper limit of the molar ratio of nitrogen to phosphorus is preferably 0.45, more preferably 0.40, and further preferably 0.38. By making the above molar ratio greater than the above lower limit and less than the above upper limit, a path conducive to lithium ion conduction is formed in the crystal structure, thereby improving ion conductivity.
[0063] Regarding the constituent elements of the solid electrolyte, the molar ratio of lithium to phosphorus (r 1), preferably 2.50, more preferably 3.00, and even more preferably 3.50. On the other hand, the upper limit of the molar ratio of lithium to phosphorus is preferably 5.50, more preferably 5.00, and even more preferably 4.50. By making the molar ratio greater than or equal to the lower limit and less than or equal to the upper limit, the precipitation temperature of HICP and the like can be easily lowered.
[0064] Regarding the constituent elements of the solid electrolyte, the lower limit of the molar ratio of sulfur to phosphorus is preferably 2.50, more preferably 3.00, and even more preferably 3.50. On the other hand, the upper limit of the molar ratio of sulfur to phosphorus is preferably 5.00, more preferably 4.50, and even more preferably 4.00. By making the above molar ratio not less than the above lower limit and not more than the above upper limit, the precipitation temperature of HICP etc. can be more easily lowered.
[0065] Regarding the constituent elements of the solid electrolyte, the lower limit of the molar ratio of aluminum to phosphorus is preferably 0.005, more preferably 0.007, and further preferably 0.010. On the other hand, the upper limit of the molar ratio of aluminum to phosphorus is preferably 0.35, more preferably 0.30, and further preferably 0.25. By making the above molar ratio not less than the above lower limit and not more than the above upper limit, the precipitation temperature of HICP etc. can be more easily lowered.
[0066] Regarding the constituent elements of the solid electrolyte, the lower limit of the molar ratio of bromine to phosphorus is preferably 0.10, more preferably 0.15, and further preferably 0.20. On the other hand, the upper limit of the molar ratio of bromine to phosphorus is preferably 1.70, more preferably 1.50, and further preferably 1.30. By making the above molar ratio greater than the above lower limit and less than the above upper limit, the precipitation temperature of HICP etc. can be more easily lowered.
[0067] Regarding the constituent elements of the solid electrolyte, the lower limit of the molar ratio of iodine to phosphorus is preferably 0.10, more preferably 0.15, and further preferably 0.20. On the other hand, the upper limit of the molar ratio of iodine to phosphorus is preferably 1.70, more preferably 1.50, and further preferably 1.30. By making the above molar ratio greater than the above lower limit and less than the above upper limit, the precipitation temperature of HICP etc. can be more easily lowered.
[0068] Regarding the constituent elements of the solid electrolyte, the lower limit of the molar ratio of the sum of bromine and iodine to phosphorus is preferably 0.30, more preferably 0.40, and further preferably 0.50. On the other hand, the upper limit of the molar ratio of the sum of bromine and iodine to phosphorus is preferably 2.10, more preferably 2.00, and further preferably 1.90. By making the above molar ratio not less than the above lower limit and not more than the above upper limit, the precipitation temperature of HICP etc. can be more easily lowered.
[0069] Regarding the constituent elements of the solid electrolyte, from the viewpoint of improving ion conductivity, it is preferred that the molar ratio of nitrogen to phosphorus is 0.01 to 0.45, and the molar ratio of the sum of bromine and iodine to phosphorus is 0.50 to 0.80 or less.
[0070] The solid electrolyte may further contain other elements other than lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine as constituent elements. As the above-mentioned other elements, alkali metal elements other than lithium, oxygen, etc. can be cited. The above-mentioned other elements also include halogen elements other than bromine and iodine. Among them, the molar ratio of the sum of the above-mentioned other elements in the solid electrolyte to phosphorus is, for example, preferably less than 0.1, more preferably less than 0.01, or substantially free of.
[0071] In one embodiment of the present invention, the solid electrolyte is preferably represented by Formula 1 below.
[0072] Li a PAl b S c N d Br e I f ···1
[0073] In the above formula 1, a, b, c, d, e and f are numerical values that give a stoichiometric ratio, a is a numerical value that satisfies 3.00<a<5.30, b is a numerical value that satisfies 0.00<b<0.40, c is a numerical value that satisfies 3.50<c<4.20, d is a numerical value that satisfies 0.00<d<0.60, e is a numerical value that satisfies 0.00<e<2.20, and f is a numerical value that satisfies 0.00<f<2.20. In this way, by expressing the solid electrolyte by the above formula 1, the precipitation temperature of HICP and the like can be easily lowered.
[0074] In one embodiment of the present invention, the solid electrolyte is also preferably represented by Formula 2 below.
[0075] (100-z 1 -z 2 ){(1-y)[xLi 2 S·(1-x)P 2 S 5 ]·yLi α Al β N}·z 1 LiBr·z 2 LiI···2
[0076] In the above formula 2, x is a value satisfying 0.50≤x≤0.80, y is a value satisfying 0<y≤0.50, and z is 1 and z2 is satisfied 5≤z 1 +z 2 ≤55 are positive values. In this way, even if the solid electrolyte is represented by the above formula 2, the precipitation temperature of HICP and the like can be easily lowered. It should be noted that the above formula 2 is a chemical formula (composition formula) representing the content ratio of each element of Li, P, Al, S, N, Br and I, and does not specify the compound as a raw material.
[0077] In the above formula 2, x more preferably satisfies 0.60≤x≤0.77, and further preferably satisfies 0.67≤x≤0.75. y more preferably satisfies 0.005≤y≤0.35, and further preferably satisfies 0.010≤y≤0.30. 1 and z 2 More preferably, 10≤z 1 +z 2 ≤40, preferably 15≤z 1 +z 2 ≤30.
[0078] In the above formula 2, the values of α and β are not particularly limited, and may be, for example, 0.80≤α≤3.0 and 0.10≤β≤1.2, or α=1.5 and β=0.5. When the solid electrolyte has such a composition, the thermal stability of HICP and the like tends to be further improved.
[0079] (Physical properties, uses, etc.)
[0080] The lower limit of the ion conductivity of the solid electrolyte at 25°C is preferably 2.0×10 -3 S / cm, more preferably 3.0×10 -3 S / cm, more preferably 4.0×10 -3 S / cm, and more preferably 5.0×10 -3 S / cm. When the ion conductivity of the solid electrolyte at 25°C is above the above lower limit, the charge and discharge performance of the storage element having the solid electrolyte can be further improved. The upper limit of the ion conductivity is not particularly limited, and is, for example, 5.0×10 -2 S / cm, which can be 2.5×10 -2 S / cm.
[0081] The shape of the solid electrolyte is not particularly limited, and is generally granular, blocky, etc. The solid electrolyte can be suitably used as an electrolyte for storage elements such as lithium ion secondary batteries, especially lithium ion storage elements. Among them, it can be particularly suitable for use as an electrolyte for all-solid batteries. It should be noted that the solid electrolyte can be used for any of the positive electrode layer, separator layer, negative electrode layer, etc. in the storage element.
[0082] <Method for producing solid electrolyte>
[0083] A method for producing a solid electrolyte according to one embodiment of the present invention comprises the steps of: preparing a composition containing lithium, phosphorus, sulfur, aluminum, nitrogen, bromine, and iodine as constituent elements; and treating the composition.
[0084] (Preparation process)
[0085] The composition used as a raw material in the manufacturing method is usually a mixture of two or more simple substances and / or compounds (hereinafter also referred to as compounds, etc.) containing at least one of lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine. Any one of the compounds contained in the above-mentioned composition (mixture) may contain lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine. One compound may contain two or more elements of lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine. For example, as a compound containing lithium and sulfur, Li 2 As compounds containing phosphorus and sulfur, there can be mentioned the following P 2 S 5 As the compound containing bromine or iodine, there can be mentioned LiBr, LiI, etc. which will be described later. The above composition may also contain a compound which does not contain any of lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine.
[0086] Examples of compounds containing lithium include Li 2 S. Li 2 O. Li 3 N.Li 2 CO 3 , metallic lithium, etc. In addition, LiBr, LiI, Li 1.5 Al 0.5 N, etc. Among them, Li 2 S, LiBr, LiI and Li 1.5 Al 0.5 N. The lithium element-containing compound or the like may be used alone or in combination of two or more.
[0087] Examples of compounds containing phosphorus include P 2 S 3 , P 2 S 5 , P 2 O 5 , P 3 N 5 , elemental phosphorus, etc. Among them, P 2 S3 and P 2 S 5 , more preferably P 2 S 5 The compound containing phosphorus element or the like may be used alone or in combination of two or more.
[0088] Examples of the compound containing sulfur include Li 2 S.P. 2 S 3 , P 2 S 5 、Al 2 S 3 、MgS、SiS 2 , elemental sulfur, etc. Among them, Li 2 S.P. 2 S 3 and P 2 S 5 , more preferably Li 2 S and P 2 S 5 The sulfur element-containing compound or the like may be used alone or in combination of two or more.
[0089] Examples of compounds containing bromine or iodine include LiBr, LiI, Br 2 ,I 2 etc. Among them, LiI and LiBr are preferred.
[0090] As the compound containing nitrogen, a compound containing nitrogen and aluminum is preferred, and a compound containing Li α Al β N γ The compound represented by (α, β and γ are numerical values giving the stoichiometric ratio). α Al β N γ The compound represented by (hereinafter also referred to as Li—Al—N containing compound) can be produced by the following steps. First, prepare Li 3 N and aluminum nitride are mixed using a mortar or the like. Next, particles of the mixed raw material compounds are manufactured. Next, the particles are heat treated to manufacture a Li-Al-N containing compound. It should be noted that the means for preparing a Li-Al-N containing compound is not limited thereto, and other methods may also be used. For example, the raw material of the Li-Al-N containing compound may be a compound containing two or more of any one of lithium, aluminum and nitrogen. The Li-Al-N containing compound may be manufactured by mechanical milling. As the Li-Al-N containing compound, a compound for industrial manufacture and sale may also be prepared.
[0091] As the Li—Al—N-containing compound, a lithium composite nitride of aluminum element can be used appropriately. As the lithium composite nitride of aluminum element, Li is preferred from the viewpoint of being easily available and suppressing the discharge of nitrogen element to the outside of the system during the manufacturing process of the solid electrolyte. 1.5 Al 0.5 N.
[0092] The above composition may further contain a compound containing aluminum and a compound containing nitrogen. Examples of the compound containing aluminum include aluminum oxides, aluminum sulfides, aluminum nitrides, and alloys of aluminum and lithium. Examples of aluminum sulfides include Al 2 S 3 、SiS 2 As nitrides of aluminum elements, for example, AlN, Si 3 N 4 、BN、Mg 3 N 2 The compound containing the aluminum element may be used alone or in combination of two or more.
[0093] For example, as an embodiment, the above composition may include Li 2 S.P. 2 S 5 , Li 1.5 Al 0.5 Composition of N, LiI and LiBr.
[0094] The preferred content of each element in the above composition is the same as the preferred content of each element in the sulfide solid electrolyte according to one embodiment of the present invention described above.
[0095] (Processing process)
[0096] In the manufacturing method, the above composition is treated to obtain a solid electrolyte. As the above treatment, there can be cited a method of obtaining an intermediate by mechanical milling or the like, and heating the intermediate. It should be noted that the means for obtaining the intermediate is not limited to this, and methods other than mechanical milling, such as a melt quenching method, etc., can also be performed.
[0097] Mechanical milling may be either dry or wet, and wet milling is preferred because the raw material compounds can be mixed more evenly. As mechanical milling, for example, a container-driven mill, a medium-stirred mill, milling using a high-speed rotating pulverizer, a roller mill, a jet mill, etc. can be cited. As a container-driven mill, for example, a rotary mill, a vibration mill, a planetary mill, etc. can be cited. As a medium-stirred mill, for example, a grinding mill, a bead mill, etc. can be cited. As milling using a high-speed rotating pulverizer, for example, a hammer mill, a pin mill, etc. can be cited. Among them, a container-driven mill is preferred, and a planetary mill is particularly preferred.
[0098] The intermediate obtained by mechanical milling or the like may have a crystalline structure, but is preferably a so-called sulfide glass. "Sulfide glass" refers to a sulfide solid electrolyte containing an amorphous structure. If the intermediate is sulfide glass, Li 2 A solid electrolyte with few low-stability crystal phases such as S and high dispersion of various elements.
[0099] Heating is heating (heat treatment) of the intermediate obtained by mechanical milling, etc. Thus, a solid electrolyte is obtained in which at least a portion of the intermediate is crystallized, preferably at least a portion is crystallized into a phase such as HICP. Heating (heat treatment) can be performed in a reduced pressure atmosphere or in an inert gas atmosphere.
[0100] The lower limit of the heating temperature is preferably T1-20[°C], more preferably T1[°C], and even more preferably T1+10[°C], based on the crystallization temperature T1 of the HICP etc. On the other hand, the upper limit of the heating temperature is preferably T1-20[°C], more preferably T1[°C], and even more preferably T1+10[°C]. 3 PS 4 The crystallization temperature T2 of the precipitation is preferably T2-20[℃], more preferably T2-30[℃], and further preferably T2-40[℃]. By making the heating temperature above the lower limit, the precipitation of HICP with high ion conductivity can be promoted. In addition, by making the heating temperature below the upper limit, the precipitation to β-Li with low ion conductivity can be suppressed. 3 PS 4 Phase transitions such as .
[0101] <Electrical storage element>
[0102] As one embodiment of the electric storage element of the present invention, an all-solid-state battery will be described below as a specific example. Figure 1The storage element 10 shown is an all-solid-state battery, which is a secondary battery in which a positive electrode layer 1 and a negative electrode layer 2 are arranged via a separator 3. The positive electrode layer 1 has a positive electrode substrate 4 and a positive electrode active material layer 5, and the positive electrode substrate 4 is the outermost layer of the positive electrode layer 1. The negative electrode layer 2 has a negative electrode substrate 7 and a negative electrode active material layer 6, and the negative electrode substrate 7 is the outermost layer of the negative electrode layer 2. Figure 1 In the illustrated electric storage device 10 , a negative electrode active material layer 6 , a separator 3 , a positive electrode active material layer 5 , and a positive electrode substrate 4 are sequentially stacked on a negative electrode substrate 7 .
[0103] The energy storage element 10 contains a solid electrolyte according to an embodiment of the present invention in at least one of the positive electrode layer 1, the negative electrode layer 2, and the separator 3. More specifically, the solid electrolyte according to an embodiment of the present invention is contained in at least one of the positive electrode active material layer 5, the negative electrode active material layer 6, and the separator 3. The energy storage element 10 contains a solid electrolyte that can improve productivity, and thus productivity can be improved.
[0104] The storage element 10 may be used in combination with other solid electrolytes other than the solid electrolyte of one embodiment of the present invention. As other solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, dry polymer electrolytes, gel polymer electrolytes, pseudo solid electrolytes, etc. other than the solid electrolyte of one embodiment of the present invention may be cited, preferably sulfide solid electrolytes. In addition, one layer of the storage element 10 may contain a plurality of different solid electrolytes, and each layer may also contain different solid electrolytes.
[0105] Examples of sulfide solid electrolytes other than the solid electrolyte of one embodiment of the present invention include Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 -LiI, Li 2 S-P 2 S 5 -LiCl, Li 2 S-P 2 S 5 -LiBr, Li 2 S-P 2 S 5 -Li 2 O. Li 2 S-P 2 S 5 -Li 2 O-LiI、Li 2 S-P 2 S 5 -Li 3 N.Li 2S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 S-B 2 S 3 , Li 2 S-P 2 S 5 -Z m S 2n (where m and n are positive numbers, and Z is any one of Ge, Zn, and Ga.) 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (where x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In.) Li 10 G 2 S 12 wait.
[0106] [Positive electrode layer]
[0107] The positive electrode layer 1 includes a positive electrode substrate 4 and a positive electrode active material layer 5 laminated on the surface of the positive electrode substrate 4. The positive electrode layer 1 may have an intermediate layer between the positive electrode substrate 4 and the positive electrode active material layer 5.
[0108] (Positive electrode substrate)
[0109] The positive electrode substrate 4 has electrical conductivity. Whether it has "electrical conductivity" is determined by a volume resistivity 10 measured in accordance with JIS-H-0505 (1975). 7Ω·cm is the threshold value for judgment. As the material of the positive electrode substrate 4, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity and cost. As the positive electrode substrate 4, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, as the positive electrode substrate 4, aluminum foil or aluminum alloy foil is preferred. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.
[0110] The average thickness of the positive electrode substrate 4 is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate 4 to the above range, the strength of the positive electrode substrate 4 can be improved, and the energy density per unit volume of the storage element 10 can be improved. The "average thickness" of the positive electrode substrate 4 and the negative electrode substrate 7 described later refers to the value obtained by dividing the mass of the substrate of a specified area by the true density and area of the substrate.
[0111] The intermediate layer is a layer disposed between the positive electrode substrate 4 and the positive electrode active material layer 5. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate 4 and the positive electrode active material layer 5. The structure of the intermediate layer is not particularly limited, and for example, it contains a binder and a conductive agent.
[0112] (Positive Electrode Active Material Layer)
[0113] The positive electrode active material layer 5 contains a positive electrode active material. The positive electrode active material layer 5 can be formed by a so-called positive electrode mixture containing a positive electrode active material. The positive electrode active material layer 5 can contain a mixture or a composite containing a positive electrode active material and a solid electrolyte. The positive electrode active material layer 5 contains any component such as a conductive agent, a binder (adhesive), a thickener, and a filler as required. One or more of these arbitrary components may not be substantially contained in the positive electrode active material layer 5.
[0114] The positive electrode active material can be appropriately selected from known positive electrode active materials. As the positive electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. Examples of the positive electrode active material include α-NaFeO 2 A lithium transition metal composite oxide having a type crystal structure, a lithium transition metal composite oxide having a spinel type crystal structure, a polyanion compound, a chalcogen compound, sulfur, etc. 2 Lithium transition metal composite oxides with a crystal structure of the type include Li[Li x Ni (1-x) ]O2 (0≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O 2 (0≤x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O 2 (0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O 2 (0≤x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O 2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O 2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Examples of lithium transition metal composite oxides having a spinel crystal structure include Li x Mn 2 O 4 , Li x Ni γ Mn (2-γ) O 4 As polyanion compounds, LiFePO 4 、LiMnPO 4 、LiNiPO 4 、LiCoPO 4 , Li 3 V 2 (PO 4 ) 3 , Li 2 MnSiO 4 , Li 2 CoPO 4 F, etc. As chalcogen compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be cited. The atoms or polyanions in these materials can also be partially replaced by atoms or anionic substances composed of other elements. The surfaces of these materials can be coated with other materials. In the positive electrode active material layer 5, one of these materials can be used alone, or two or more of them can be mixed and used.
[0115] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably 0.1 μm to 20 μm, for example. By making the average particle size of the positive electrode active material above the above lower limit, the manufacture or handling of the positive electrode active material becomes easy. By making the average particle size of the positive electrode active material below the above upper limit, the electron conductivity of the positive electrode active material layer 5 is improved. It should be noted that when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. "Average particle size" refers to the particle size distribution measured by the laser diffraction / scattering method based on the diluted solution after the particles are diluted in a solvent in accordance with JIS-Z-8825 (2013), and the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%.
[0116] In order to obtain a powder with a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow jet mill, or a sieve can be cited. When pulverizing, wet pulverization in which an organic solvent such as water or hexane coexists can be used. As a classification method, a sieve, a wind classifier, etc. can be used together with a dry method or a wet method as needed.
[0117] The content of the positive electrode active material in the positive electrode active material layer 5 is preferably 10 mass % to 95 mass %, and the lower limit is more preferably 30 mass %, and further preferably 50 mass %. When the content of the positive electrode active material is within the above range, the capacity of the energy storage device 10 can be increased.
[0118] When the positive electrode active material layer 5 contains a solid electrolyte, the content of the solid electrolyte is preferably 5% to 90% by mass, more preferably 20% to 70% by mass, and the upper limit is sometimes further preferably 50% by mass. By making the content of the solid electrolyte within the above range, the capacitance of the storage element 10 can be increased. When the solid electrolyte of one embodiment of the present invention is used in the positive electrode active material layer 5, the content of the solid electrolyte of one embodiment of the present invention relative to the total solid electrolyte in the positive electrode active material layer 5 is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and further preferably substantially 100% by mass.
[0119] The mixture of the positive electrode active material and the solid electrolyte is a mixture made by mixing the positive electrode active material and the solid electrolyte by mechanical milling. For example, the mixture of the positive electrode active material and the solid electrolyte can be obtained by mixing a particulate positive electrode active material and a particulate solid electrolyte. As the composite of the positive electrode active material and the solid electrolyte, there can be cited a composite having a chemical or physical bond between the positive electrode active material and the solid electrolyte, a composite obtained by mechanically compounding the positive electrode active material with the solid electrolyte, etc. The composite contains the positive electrode active material and the solid electrolyte in one particle, for example, the positive electrode active material and the solid electrolyte form an aggregated state, and a film containing the solid electrolyte is formed on at least a portion of the surface of the positive electrode active material.
[0120] The conductive agent is not particularly limited as long as it is a material with conductivity. As such a conductive agent, for example, carbonaceous materials, metals, conductive ceramics, etc. can be mentioned. As carbonaceous materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be mentioned. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be mentioned. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be mentioned. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be mentioned. As the shape of the conductive agent, powder, fiber, etc. can be mentioned. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can also be used in a composite. For example, a material after a composite of carbon black and CNT can be used. Among these, from the viewpoint of electronic conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.
[0121] The content of the conductive agent in the positive electrode active material layer 5 is preferably 1% to 10% by mass, and more preferably 3% to 9% by mass. When the content of the conductive agent is within the above range, the energy density of the electric storage device 10 can be increased.
[0122] Examples of adhesives include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.
[0123] The content of the binder in the positive electrode active material layer 5 is preferably 1% by mass to 10% by mass, and more preferably 3% by mass to 9% by mass. When the content of the binder is within the above range, the active material can be stably retained.
[0124] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be inactivated in advance by methylation or the like.
[0125] The filler is not particularly limited. As the filler, there can be mentioned polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other materials derived from mineral resources or their artificial products, etc.
[0126] The positive electrode active material layer 5 may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, etc., typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, etc., and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, W, etc. as components other than the positive electrode active material, solid electrolyte, conductive agent, binder, thickener, and filler.
[0127] The average thickness of the positive electrode active material layer 5 is preferably 30 μm to 1000 μm, and more preferably 60 μm to 500 μm. By making the average thickness of the positive electrode active material layer 5 greater than the above lower limit, a storage element 10 having a high energy density can be obtained. By making the average thickness of the positive electrode active material layer 5 less than the above upper limit, miniaturization of the storage element 10 can be sought. The average thickness of the positive electrode active material layer 5 is set to the average value of the thickness measured at any five locations. The same applies to the average thickness of the negative electrode active material layer 6 and the isolation layer 3 described later.
[0128] [Negative electrode layer]
[0129] The negative electrode layer 2 includes a negative electrode substrate 7 and a negative electrode active material layer 6 disposed directly or via an intermediate layer on the negative electrode substrate 7. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified for the positive electrode layer 1, for example.
[0130] (Negative electrode substrate)
[0131] The negative electrode substrate 7 has conductivity. As the material of the negative electrode substrate 7, metals such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or their alloys, carbonaceous materials, etc. can be used. Among these, copper or copper alloys are preferred. As the negative electrode substrate 7, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate 7, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.
[0132] The average thickness of the negative electrode substrate 7 is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate 7 to be within the above range, the strength of the negative electrode substrate 7 can be increased, and the energy density per unit volume of the storage element 10 can be increased.
[0133] (Negative Electrode Active Material Layer)
[0134] The negative electrode active material layer 6 contains a negative electrode active material. The negative electrode active material layer 6 can be formed of a so-called negative electrode mixture containing a negative electrode active material. The negative electrode active material layer 6 can contain a mixture or a composite containing a negative electrode active material and a solid electrolyte. The negative electrode active material layer 6 contains any components such as a conductive agent, a binder, a thickener, and a filler as needed. The types and preferred contents of the arbitrary components of these negative electrode active material layers 6 are the same as those of the above-mentioned arbitrary components of the positive electrode active material layer 5. One or more of these arbitrary components may not be substantially contained in the negative electrode active material layer 6.
[0135] The negative electrode active material layer 6 may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, etc., typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, etc., and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, W, etc. as components other than the negative electrode active material, solid electrolyte, conductive agent, binder, thickener, and filler.
[0136] The negative electrode active material can be appropriately selected from known negative electrode active materials. As the negative electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxides, Ti oxides, and Sn oxides; Li 4 Ti 5 O 12 、LiTiO 2 、TiNb 2 O 7Titanium-containing oxides such as titanium oxides; polyphosphate compounds; silicon carbide; carbon materials such as graphite and non-graphite carbon (graphitizable carbon or non-graphitizable carbon). Among these materials, graphite and non-graphite carbon are preferred. In the negative electrode active material layer 6, one of these materials may be used alone, or two or more of them may be mixed and used.
[0137] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before or during charge / discharge. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the perspective of obtaining a material with stable physical properties, artificial graphite is preferred.
[0138] “Non-graphite carbon” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge / discharge or during discharge. 002 ) is a carbon material having a carbon thickness of 0.34 nm to 0.42 nm. Examples of non-graphite carbon include difficult-graphitization carbon and easy-graphitization carbon. Examples of non-graphite carbon include materials derived from resins, petroleum asphalt or materials derived from petroleum asphalt, petroleum coke or materials derived from petroleum coke, materials derived from plants, materials derived from alcohols, and the like.
[0139] Here, the "discharge state" refers to a state in which the carbon material as the negative electrode active material is discharged in a manner that lithium ions that can be absorbed and released during charging and discharging are fully released. For example, the following state: in a monopolar battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li as a counter electrode, the open circuit voltage is 0.7V or more.
[0140] "Difficult to graphitize carbon" refers to the above-mentioned 002 It is a carbon material with a diameter of 0.36nm to 0.42nm.
[0141] "Easily graphitizable carbon" refers to the above-mentioned 002 A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm.
[0142] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be set to, for example, 1 nm to 100 μm. When the negative electrode active material is a carbon material, a titanium-containing oxide or a polyphosphate compound, its average particle size can be 1 μm to 100 μm. When the negative electrode active material is Si, Sn, Si oxide or Sn oxide, etc., its average particle size can be 1 nm to 1 μm. By making the average particle size of the negative electrode active material above the above lower limit, the manufacture or handling of the negative electrode active material becomes easy. By making the average particle size of the negative electrode active material below the above upper limit, the electronic conductivity of the negative electrode active material layer 6 is improved. In order to obtain a powder with a specified particle size, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected from the methods exemplified in the positive electrode layer 1, for example. When the negative electrode active material is a metal such as metal Li, the negative electrode active material can be in the form of foil.
[0143] The content of the negative electrode active material in the negative electrode active material layer 6 is preferably 10 mass % to 95 mass %, and the lower limit is more preferably 30 mass %, and further preferably 50 mass %. When the content of the negative electrode active material is within the above range, the capacity of the energy storage device 10 can be increased.
[0144] When the negative electrode active material layer 6 contains a solid electrolyte, the content of the solid electrolyte is preferably 5% to 90% by mass, more preferably 20% to 70% by mass, and the upper limit is sometimes further preferably 50% by mass. By making the content of the solid electrolyte within the above range, the capacitance of the storage element 10 can be increased. When the negative electrode active material layer 6 uses a solid electrolyte of one embodiment of the present invention, the content of the solid electrolyte of one embodiment of the present invention relative to the total solid electrolyte in the negative electrode active material layer 6 is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and further preferably substantially 100% by mass.
[0145] The mixture or composite of the negative electrode active material and the solid electrolyte may be a mixture or composite in which the positive electrode active material is replaced with the negative electrode active material in the mixture or composite of the positive electrode active material and the solid electrolyte.
[0146] The average thickness of the negative electrode active material layer 6 is preferably 30 μm to 1000 μm, and more preferably 60 μm to 500 μm. By making the average thickness of the negative electrode active material layer 6 equal to or greater than the above lower limit, a storage element 10 having a high energy density can be obtained. By making the average thickness of the negative electrode active material layer 6 equal to or less than the above upper limit, the storage element 10 can be miniaturized.
[0147] [Isolation layer]
[0148] The separator 3 contains a solid electrolyte. As the solid electrolyte contained in the separator 3, in addition to the solid electrolyte of one embodiment of the present invention described above, various solid electrolytes can be used, among which a sulfide solid electrolyte is preferably used. The content of the solid electrolyte in the separator 3 is sometimes preferably 70% by mass or more, more preferably 90% by mass or more, further preferably 99% by mass or more, and further preferably substantially 100% by mass. In addition, when the solid electrolyte of one embodiment of the present invention is used in the separator 3, the content of the solid electrolyte of one embodiment of the present invention in the total solid electrolyte in the separator 3 is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and further preferably substantially 100% by mass.
[0149] The isolation layer 3 may contain Li 3 PO 4 Phosphoric acid compounds, oxides, halides, binders, thickeners, fillers and other optional components. The binders, thickeners, fillers and other optional components can be selected from the materials exemplified in the positive electrode active material layer 5 .
[0150] The average thickness of the separator 3 is preferably 1 μm to 50 μm, and more preferably 3 μm to 20 μm. When the average thickness of the separator 3 is greater than or equal to the above lower limit, the positive electrode layer 1 and the negative electrode layer 2 can be insulated with high reliability. When the average thickness of the separator 3 is less than or equal to the above upper limit, the energy density of the storage element 10 can be increased.
[0151] The storage element of this embodiment can be installed as a storage unit (battery module) composed of a plurality of storage elements in a vehicle power source such as an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), a power source for electronic equipment such as a personal computer, a communication terminal, or a power source for storing electricity. In this case, the technology of the present invention can be applied to at least one storage element included in the storage unit.
[0152] Figure 2 An example of an electric storage device 30 is shown in which an electric storage unit 20 formed by collecting two or more electrically connected electric storage elements 10 is further collected. The electric storage device 30 may include a bus bar (not shown) that electrically connects the two or more electric storage elements 10, a bus bar (not shown) that electrically connects the two or more electric storage units 20, etc. The electric storage unit 20 or the electric storage device 30 may include a state monitoring device (not shown) that monitors the state of one or more electric storage elements.
[0153] <Method for manufacturing energy storage device>
[0154] The method for manufacturing a storage element according to an embodiment of the present invention can be performed by a generally known method, except that a solid electrolyte according to an embodiment of the present invention is used as part or all of the solid electrolyte in the production of at least one of the positive electrode layer, the separator layer, and the negative electrode layer. Specifically, the manufacturing method comprises, for example: (1) preparing a positive electrode mixture, (2) preparing a material for a separator layer, (3) preparing a negative electrode mixture, and (4) stacking a positive electrode layer, a separator layer, and a negative electrode layer. Each step is described in detail below.
[0155] (1) Positive electrode mixture preparation process
[0156] In this process, a positive electrode mixture that is usually used to form a positive electrode layer (positive electrode active material layer) is prepared. There is no particular limitation on the method for preparing the positive electrode mixture, and it can be appropriately selected according to the purpose. For example, mechanical milling treatment of the material of the positive electrode mixture, compression molding of the positive electrode active material, sputtering of the positive electrode active material using a target material, etc. can be cited. In the case where the positive electrode mixture contains a mixture or a composite containing a positive electrode active material and a solid electrolyte, this process includes, for example: mixing the positive electrode active material and the solid electrolyte using a mechanical milling method, etc., to prepare a mixture or a composite of the positive electrode active material and the solid electrolyte.
[0157] (2) Preparation process of materials for isolation layer
[0158] In this process, a material for an isolation layer that is usually used to form an isolation layer is prepared. In the case where the storage element is an all-solid-state battery, the material for the isolation layer can be a solid electrolyte. The solid electrolyte used as the isolation layer material can be prepared by a conventionally known method. For example, it can be obtained by processing a specified material by a mechanical milling method. The material for the isolation layer can be prepared by heating the specified material to a temperature above the melting point by a melt quenching method, and the two are melt-mixed and quenched at a specified ratio. As a synthesis method of other isolation layer materials, for example, a solid phase method of calcining under reduced pressure and sealing, a liquid phase method such as dissolution and precipitation, a gas phase method (PLD), calcining in an argon atmosphere after mechanical milling, etc. can be cited.
[0159] (3) Negative electrode mixture preparation process
[0160] In this process, a negative electrode mixture is prepared, which is usually used to form a negative electrode layer (negative electrode active material layer). The specific method for preparing the negative electrode mixture is the same as that for the positive electrode mixture. In the case where the negative electrode mixture contains a mixture or a composite comprising a negative electrode active material and a solid electrolyte, this process includes, for example: mixing the negative electrode active material and the solid electrolyte using a mechanical milling method, etc., to prepare a mixture or a composite of the negative electrode active material and the solid electrolyte.
[0161] (4) Lamination process
[0162] In this process, for example, a positive electrode layer having a positive electrode substrate and a positive electrode active material layer, a separator layer, and a negative electrode layer having a negative electrode substrate and a negative electrode active material layer are stacked. In this process, the positive electrode layer, the separator layer and the negative electrode layer can be formed in this order, or vice versa, and the formation order of each layer is not particularly limited. The above-mentioned positive electrode layer is formed, for example, by press-molding the positive electrode substrate and the positive electrode mixture, the above-mentioned separator layer is formed by press-molding the separator layer material, and the above-mentioned negative electrode layer is formed by press-molding the negative electrode substrate and the negative electrode mixture. The positive electrode layer, the separator layer and the negative electrode layer can be stacked by press-molding the positive electrode substrate, the positive electrode mixture, the separator layer material, the negative electrode mixture and the negative electrode substrate at one time. The positive electrode layer and the negative electrode layer can also be pre-molded separately and laminated by press-molding with the separator layer.
[0163] [Other embodiments]
[0164] It should be noted that the nonaqueous electrolyte storage element of the present invention is not limited to the above-mentioned embodiment, and various changes can be made within the scope of the gist of the present invention. For example, the structure of other embodiments can be added to the structure of one embodiment, and in addition, a part of the structure of one embodiment can be replaced with the structure of other embodiments or known technology. Furthermore, a part of the structure of one embodiment can be deleted. In addition, known technology can be added to the structure of one embodiment.
[0165] For example, the storage element of the present invention may also include other layers in addition to the positive electrode layer, the separator layer and the negative electrode layer. In addition, the storage element of the present invention may also contain a liquid. As such a storage element, for example, a storage element in which the gaps between the positive electrode active material layer 5, the separator layer 3 and the negative electrode active material layer 6 of the above-mentioned storage element 10 are filled with a non-aqueous electrolyte containing an ionic liquid or the like can be cited. In addition to being a storage element of a secondary battery, the storage element of the present invention may also be a capacitor or the like.
[0166] <Example>
[0167] Hereinafter, the present invention will be further specifically described by way of examples, but the present invention is not limited to the following examples.
[0168] [Example 1]
[0169] The solid electrolyte satisfying the composition ratio described in Table 1 was synthesized by the following treatment. Li and Mg were weighed so as to have a molar ratio of 1.2:1. 3 N and AlN were mixed in a mortar and pelletized. Then, heat treatment was performed at 750°C for 1 hour to produce Li 1.5 Al 0.5 N. These steps were carried out in an argon atmosphere with a dew point of -50°C or less. X-ray diffraction measurement confirmed that the produced Li 1.5Al 0.5 The main phase of N is Li 1.5 Al 0.5 N.
[0170] In a glove box of an argon atmosphere with a dew point of -50°C or less, Li was weighed so that the molar ratio was 51.00:17.00:12.00:12.00:8.00. 2 S(99.98%, Aldrich), P 2 S 5 (99%, made by Aldrich), Li 1.5 Al 0.5 N, LiBr (99.999%, manufactured by Aldrich) and LiI (99.999%, manufactured by Aldrich) were then mixed in a mortar to prepare a composition containing lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine as constituent elements.
[0171] The composition was placed in a sealed 80 mL zirconia jar containing 160 g of zirconia balls with a diameter of 4 mm, and subjected to mechanical milling treatment at 510 rpm for 45 hours using a planetary ball mill (FRITSCH, model: Premium line PL-7) to obtain an intermediate.
[0172] The intermediate was heated (heat treated) at 200°C for 2 hours to obtain the solid electrolyte of Example 1. The heat treatment temperature HT[°C] was set to be within the range of T1-20°C or higher and T2-20°C or lower based on the crystallization temperature T1[°C] and the crystallization temperature T2[°C]. It should be noted that the crystallization temperature T1[°C] and the crystallization temperature T2[°C] can be obtained by taking out a part of the intermediate after the mechanical milling treatment and performing DSC measurement using the above method.
[0173] [Examples 2 to 40, Comparative Examples 1 to 14]
[0174] Solid electrolytes of Examples 2 to 40 and Comparative Examples 1 to 14 were obtained in the same manner as in Example 1 except that the composition ratios of the solid electrolytes were as shown in Tables 1 to 4. Each heat treatment temperature HT [° C.] was set in the same manner as in Example 1.
[0175] Regarding the constituent elements of the solid electrolytes of Examples 1 to 40 and Comparative Examples 1 to 14, the molar ratio of lithium to phosphorus was set to r. 1 The molar ratio of the sum of bromine and iodine to phosphorus is r 2 When r 1 -r 2 , the molar ratio of lithium to phosphorus Li / P (r 1), the molar ratio of sulfur to phosphorus S / P, the molar ratio of aluminum to phosphorus Al / P, the molar ratio of nitrogen to phosphorus N / P, the molar ratio of bromine to phosphorus Br / P, the molar ratio of iodine to phosphorus I / P, the molar ratio of the sum of bromine and iodine to nitrogen r 3 They are shown in Tables 1 to 4. In addition, regarding the solid electrolytes of Examples 1 to 40 and Comparative Examples 1 to 14, the crystallization temperature T1 [°C], the crystallization temperature T2 [°C], the difference in crystallization temperature T2-T1 [°C], the heat treatment temperature HT [°C], and the crystal structure confirmed by the X-ray diffraction pattern obtained by the powder X-ray diffraction measurement by the above method are shown in Tables 1 to 4.
[0176] [evaluate]
[0177] The AC impedance was measured by the above method using "VMP-300" manufactured by Bio-Logic, and the ion conductivity (σ 25 ). The respective measurement results are shown in Tables 1 to 4.
[0178] surface
[0179]
[0180] [Table 2]
[0181]
[0182] [Table 3]
[0183]
[0184] [Table 4]
[0185]
[0186] As shown in Tables 1 and 2, when r 1 -r 2 When r is 3.00~3.60, 3 Examples 1 to 30 with r of 1.5 to 100 3 The crystallization temperature T1 is lower than that of Comparative Examples 1 to 3, which are less than 1.5. The crystallization temperature T1 of Examples 1 to 30 is 203° C. or less. Therefore, the productivity can be improved.
[0187] As shown in Table 3, when r 1 -r 2 When it is 2.80 or more and less than 3.00, r 3 Examples 31 to 39 with a value of 2.0 to 100 and Comparative Examples 4 to 6 without iodine, Comparative Examples 7 and 8 without bromine, 3The crystallization temperature T1 is lower than that of Comparative Examples 9 to 11, which are less than 2.0. The crystallization temperature T1 of Examples 31 to 39 is 203° C. or less. Therefore, the productivity can be improved.
[0188] As shown in Table 4, r 1 -r 2 is 2.60 or more and less than 2.80 and r 3 Example 40 with r of 2.5 to 100 1 -r 2 Comparative Example 12 with a value less than 2.6, and r 1 -r 2 is 2.6 or more and less than 2.8 and r 3 The crystallization temperature T1 of Comparative Example 13, which is less than 2.5, is lower than that of Comparative Example 14. The crystallization temperature T1 of Example 40 is 203° C. or less. Therefore, the productivity can be improved.
[0189] The solid electrolyte of the present invention can be suitably used as a solid electrolyte for power storage devices such as all-solid-state batteries.
[0190] Explanation of symbols
[0191] 1. Positive electrode layer
[0192] 2 Negative electrode layer
[0193] 3 Isolation layer
[0194] 4. Cathode substrate
[0195] 5 Positive electrode active material layer
[0196] 6 Negative electrode active material layer
[0197] 7 Negative electrode substrate
[0198] 10 Energy storage element (all-solid-state battery)
[0199] 20 Storage unit
[0200] 30 Power storage device
Claims
1. A solid electrolyte comprising lithium, phosphorus, sulfur, aluminum, nitrogen, bromine and iodine as constituent elements and having a crystal structure, When the molar ratio of the lithium to the phosphorus is r1, the molar ratio of the sum of the bromine and the iodine to the phosphorus is r2, and the molar ratio of the sum of the bromine and the iodine to the nitrogen is r3, the following conditions (a), (b) or (c) are satisfied: (a) 3.00≤r1-r2≤3.60 and 1.5≤r3≤100 (b) 2.80≤r1-r2<3.00 and 2.0≤r3≤100 (c)2.60≤r1-r2<2.80 and 2.5≤r3≤100.
2. The solid electrolyte according to claim 1, wherein The molar ratio of the nitrogen to the phosphorus is 0.01 to 0.
45.
3. The solid electrolyte according to claim 1 or 2, which is represented by the following formula 1: Li a PAl b S c N d Br e I f ···1 in, In Formula 1, a, b, c, d, e and f are values giving the stoichiometric ratio, a is a value satisfying 3.00<a<5.30, b is a value satisfying 0.00<b<0.40, c is a value satisfying 3.50<c<4.20, d is a value satisfying 0.00<d<0.60, e is a value satisfying 0.00<e<2.20, and f is a value satisfying 0.00<f<2.
20.
4. The solid electrolyte according to claim 1 or 2, wherein There are multiple crystallization temperatures in the range of 150°C to 400°C, and when the lowest crystallization temperature among the multiple crystallization temperatures is set to T1[°C] and the highest crystallization temperature among the multiple crystallization temperatures is set to T2[°C], the difference {T2-T1} between the crystallization temperature T1 and the crystallization temperature T2 is greater than 50°C.
5. The solid electrolyte according to claim 1 or 2, wherein The present invention comprises at least one of a crystal structure A having diffraction peaks at 2θ=19.9°±0.5° and 29.3°±0.5° in an X-ray diffraction pattern using CuKα rays, and a crystal structure B having diffraction peaks at diffraction angles 2θ=21.0±0.5° and 28.0±0.5° in the X-ray diffraction pattern.
6. The solid electrolyte according to claim 5, wherein Contains the crystal structure A.
7. The solid electrolyte according to claim 1 or 2, wherein The ionic conductivity at 25°C is 2.0×10 -3 S / cm or more.
8. An electric storage element comprising the solid electrolyte according to claim 1 or 2.
9. A method for producing a solid electrolyte, comprising the following steps: preparing a composition containing lithium, phosphorus, sulfur, aluminum, nitrogen, bromine, and iodine as constituent elements; and treating the composition; When the molar ratio of the lithium to the phosphorus is r1, the molar ratio of the sum of the bromine and the iodine to the phosphorus is r2, and the molar ratio of the sum of the bromine and the iodine to the nitrogen is r3, the following conditions (a), (b) or (c) are satisfied: (a) 3.00≤r1-r2≤3.60 and 1.5≤r3≤100 (b) 2.80≤r1-r2<3.00 and 2.0≤r3≤100 (c)2.60≤r1-r2<2.80 and 2.5≤r3≤100.
Citation Information
Patent Citations
Method for manufacturing sulfide solid electrolyte, sulfide solid electrolyte, all-solid battery, and method for selecting raw material compound used to manufacture sulfide solid electrolyte
WO2020045634A1
